Análise comparativa dos resultados analíticos dos ensaios toxicológicos do núcleo de laboratórios forense- NULF/IPC de Campina Grande-PB (Revista Brasileira Multidisciplinar, 2024)
Forensic toxicology uses quantitative and qualitative analytical techniques to analyze the collected samples, using screening and definitive tests for the final result with efficiency in the detection of toxic substances. One must know the dynamics of forensic toxicology laboratories in order to help define their analytical needs and ensure the basic precepts of analytical credibility. Thus, the present work aims to trace the analytical profile of the NULF- CG over the last five years. A descriptive research was carried out with a quantitative approach and document analysis. All death records registered at the NULF36CG were analyzed. Among the years under study, there was a decrease in the number of cases over the period studied. Males had the highest number of cases within the analyzed periods, with 69.07% in the years 2017 to 2021. The age group with the highest prevalence was 31–40 years, with 25.19% between the years of 2017 and 2021 and a 78.15% prevalence of requests for post-mortem toxicological tests. Blood was the most used biological sample with 32.52% between the years, and the most used substance class in the years 2017 to 2021 was pesticides, and the most used substance was Carbofuran. Through the results, it was possible to gain clarity about the importance of standardizing toxicological analyses in all their phases, being able to invest in other equipment, and increasing the power of the identification of substances in toxicological analyses.